ROLA KRAJOWEJ INFRASTRUKTURY GAZOWEJ W KSZTAŁTOWANIU WSPÓŁCZESNEGO BEZPIECZEŃSTWA ENERGETYCZNEGO POLSKI - Mróz, Maciej (Polityka i Społeczeństwo, 2020)
Electricity is one of the factors shaping the quality of life of society. The Polish Energy sector is to a large extent identified with fossil fuel used in conventional energy, based mainly on hard coal, which is not fully in line with the current energy policy of the European Union. Therefore, today it is necessary to use renewable energy more efficiently, which, in addition to the clearly indicated economic effect, also accentuates environmental effects. The purpose of the work is to show the opinions of young people aged 15–24 in terms of their awareness of the interpretation of myths about renewable energy, which is a key problem in the development of the modern energy sector, and to indicate the directions of development of the energy policy in Poland